PATTERN OF RELATIONSHIPS AMONG PRODUCTIVITY AND NUTRITIONAL TRAITSIN PEARL MILLET (Pennisetum Glaucum (L.) R. Br.) - K. SUPRIYA; ANIL KUMAR VEMULA, VIJAYAKUMAR KORABOYANA, ESWARI KANCHERLA, S. N. C. V. L. PUSHPAVALLI (The Journal of Research, PJTSAU, 2026)
The present investigation was carried out to study the correlation and path analysis amonggrain yield, yield-related and nutritional traits in pearl millet hybrids. This experiment was conducted in a total of 168 hybrids, which were developed by crossing 84 advanced generation seed parental (B) lines with two restorer (R) line testers by line x tester mating design. These hybrids were evaluated in 4 trials (each with 42 hybrids) during rainy season of 2020 at four locations. Observations were recorded on days to 50% flowering, plant height, 1000-seed weight, grain iron content, grain zinc content and grain yield. Correlation analysis revealed that significant positive correlation was found between grain yield and plant height; days to 50% flowering and plant height; and grain Fe and Zn content. Significant negative correlation was observed between grain yield with grain Fe and Zn content. The results of path analysis showed that plant height showed highest direct effect and days to 50% flowering showed highest indirect effects on grain yield. These results suggests that plant height and days to 50% flowering should be given maximum consideration for total grain yield improvement.